2014
DOI: 10.1111/ane.12280
|View full text |Cite
|
Sign up to set email alerts
|

The teratogenicity of the newer antiepileptic drugs - an update

Abstract: Evidence from this and other studies suggests that lamotrigine and levetiracetam have low risk for teratogenesis, but that topiramate exposure early in pregnancy may be associated with dose-related anatomical teratogenesis, as valproate is already known to be.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 16 publications
6
74
0
7
Order By: Relevance
“…Of the 13 studies investigating major malformations, ten controlled for factors that play an important part in the occurrence or prevention of birth defects [27,28], such as FA supplementation or chromosomal abnormalities [21,24,[29][30][31][32][33][34][35][36], and 12 studies controlled for additional relevant factors such as maternal age, family history of congenital malformations [37,38], or alcohol consumption [39] during pregnancy [21,24,[29][30][31][32][33][34][35][36][40][41][42]. Six of those studies reported the general timing of the fetal exposure [24,29,31,33,35,42], five recorded the dosage of lamotrigine that subjects were taking [24,30,33,34,41], and three stated the severity of the underlying disease, i.e., frequency of epileptic seizures during the pregnancy [21,32,34]. While two of the studies [21,34] reported the frequency of women experiencing epileptic seizures (2...…”
Section: Comparabilitymentioning
confidence: 99%
“…Of the 13 studies investigating major malformations, ten controlled for factors that play an important part in the occurrence or prevention of birth defects [27,28], such as FA supplementation or chromosomal abnormalities [21,24,[29][30][31][32][33][34][35][36], and 12 studies controlled for additional relevant factors such as maternal age, family history of congenital malformations [37,38], or alcohol consumption [39] during pregnancy [21,24,[29][30][31][32][33][34][35][36][40][41][42]. Six of those studies reported the general timing of the fetal exposure [24,29,31,33,35,42], five recorded the dosage of lamotrigine that subjects were taking [24,30,33,34,41], and three stated the severity of the underlying disease, i.e., frequency of epileptic seizures during the pregnancy [21,32,34]. While two of the studies [21,34] reported the frequency of women experiencing epileptic seizures (2...…”
Section: Comparabilitymentioning
confidence: 99%
“…MCM rates are reported as 4.2 % to 4.9 % for monotherapy use, with an increased risk of cleft lip and cleft palate and hypospadias [11,12]. The Australian pregnancy register reported a particularly high rate of MCMs for TPM when used as polytherapy, at 14.1 % with a relative risk of 4.32 (95 % CI 1.57-11.05) compared with no AED exposure [13]. Another major concern is a high rate of small for gestational age (SGA) births following in utero exposure to TPM; the NAAPR reported that 17.9 % of TPMexposed infants were SGA with a relative risk of 2.4 (95 % CI 1.8-22) compared with LTG [14].…”
Section: Tpmmentioning
confidence: 99%
“…Converging evidence from registry studies indicates that teratogenic risks are higher with valproate, followed by carbamazepine and topiramate. Among other commonly prescribed AEDs, older generation agents such as phenobarbitone and phenytoin have been associated with higher risks compared with lamotrigine, levetiracetam, clonazepam and gabapentin (Vajda et al, 2014;Voinescu and Pennell, 2015). Evidence-based recommendations include the avoidance of valproate and AED polytherapy during pregnancy, especially during the first trimester, in order to reduce the risk of congenital malformations.…”
Section: Women With Epilepsy: Clinically Relevant Issuesmentioning
confidence: 99%